Study on milk yield and composition in Mehsana goat - K. P. Singh; H. H. Panchasar; Sanjay Kumar; A. C. Patel; G.B. Solanki; P. K. Patel; Solanki, K.G. (Journal of Livestock Biodiversity, 2025)
Present study was carried out on 417 monthly milk records to evaluate milk production performance and colostrums and milk composition in Mehsana goat maintained at Sheep and Goat Research Station of Sardarkrushinagar Agricultural University, Gujarat, during the year 2007-08. The total lactation milk yield in Mehsana goat was 76.35 ± 1.67 kg. The highest monthly milk yield was observed in the month of August (16.69 ± 1.74 kg) and lowest in December (8.16 ± 1.14 kg).The overall means ± SE for fat, SNF and protein in colostrum were 5.74 ± 0.41, 12.72 ± 0.59 and 5.09 ± 0.41 percent, respectively. The corresponding estimates in milk were 3.23 ± 0.07, 8.07 ± 0.04 and 3.15 ± 0.02 percent, respectively. High SNF percent in milk was found during early and late stages of lactation, while high fat content was observed during summer months.